IN VITRO PROTEIN DIGESTIBILITY OF MILLET BASED SOUTH INDIAN BREAKFAST PREPARATIONS - V. DURGA RANI, JANE BRIDGET KANDEH, UMA DEVI K K. UMA MAHESWARI, T. SARAH KAMALA and (The Journal of Research, PJTSAU, 2019)
Millet grains are now receiving specific attention from the point of nutrition security and the importance of utilization millets as food is increasing in the 21st Century. Six varieties of millets have been developed and standardized to serve as most common breakfast dishes namely idly, dosa and upma using traditional recipe. The overall mean IVPD of idlys from 6 millets was 78.67±4.36% and IVPD of millet idly was significantly high (P<0.01) compared to the respective mean IVPD of millet dosa and millet upma in the decreasing order. Mean IVPD of dosa breakfast from 6 millets was 71.51±6.58% and the in vitro protein digestibility of millet dosa was significantly higher than IVPD of millet upma (P<0.01) but significantly low compared to millet idly (P<0.01), indicating that millet dosa stands next to millet idly in its protein digestibility. The mean IVPD of upma from 6 millets was 61.76 ± 2.43% and it was significantly lower (P<0.01) than that of millet idly and dosa. Fermentation in idly and dosa batters improved IVPD to a great extent. The in vitro protein digestibility of proso millet and foxtail millet products was high compared to pearl millet, little millet, sorghum and finger millet. Higher in vitro protein digestibility of proso millet upma may be due to the low anti-nutrients and inhibitors like phyates and polyphenol content of proso millet.